A COMPARATIVE STUDY OF INDIRECT METHODS OF TIME AND FREQUENCY CHARACTERISTICS MEASUREMENT OF THE LINEAR OBJECT IN THE SIMULATION MODEL - Gavryliuk, V. I.; Bezrukov, V. V.; Rybalka, R. V. (Science and Transport Progress, 2007)
On the basis of the developed imitating model and the carried out modeling it is shown, that using developed method allow to receive sufficient for practical use accuracy of system characteristics measurements of automatics and communication lines.